ANALISIS KURIKULUM 2013 DITINJAU DARI ASPEK NILAI KARAKTER BANGSA - Muhtar, Tatang (Universitas Pendidikan Indonesia, 2014)
National education is still experiencing difficulties in producing quality graduates, skilled, and creative that can serve as a driving source in various fields of development. And outputs the result of education is often a burden on the government to meet their needs for social services, employment, subsidies, and the like. They pass and emerge as new citizens who are not able to offer a solution, but rather a source of trouble and anxiety community. One source of problems in education is still weak education that can cultivate the essential values of humanity. Where today there has been a separation between